Psychoeducational Therapy as a Nursing Intervention in Preparing Families and Adolescents Inmates toward Release - wilma, Wilma; Syarif, Iqwan; Rahmawati; Krisna Murti, Kafita (Journal of Educational, Health and Community Psychology, 2025)
Families face several psychosocial problems that affect their ability to plan and care for adolescent inmates. This research to determine the effect of family psychoeducational therapy on the ability of families to care for adolescent inmates and satisfaction with nursing services. The quasi-experimental pre-post test was used with a control group, in July-September 2024. The intervention group received five sessions of therapy, and the control group received general nursing services. The sampling technique was random permutation. Data measurement using an instrument observation and evaluation psychoeducational therapy and analyzed using Statistical Product and Service Solutions. Family satisfaction before and after intervention showed a significant increase (p-value 0.001) and the control group showed an insignificant increase. The family's ability before and after intervention significantly increased (p-value 0.001) and control group showed an insignificant increase. Comprehensive nursing practice in preparing families of adolescent inmates will contribute to preventing recidivism.